2014
DOI: 10.9734/ijbcrr/2014/7382
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Values in Sheep Fed a Diet Containing Black Cumin (Nigella sativa) Seed Oil

Abstract: The aim of this study was to investigate changes in hematological values after feeding diet mixed with oil pressed from seeds of Nigella sativa in sheep. The results indicated that there was no effect on the total Red Blood Cells (RBCs) count due to treatment when compared to the control group, but the treated group showed significant (P≤0.05) increase in the total RBCs count after six weeks compared to the transient decrease at week two. Hemoglobin concentration showed similar pattern to what was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(8 reference statements)
2
4
0
Order By: Relevance
“…Data in Table (7) eleducated that Hb values were nearly similar in different groups (12.55, 12.42 and 12.24 g/dL for G3, G2 and control group, respectively). These findings matches with those reported by Abd El-Halim et al (2014) who found that Hb values did not differ between sheep fed on diet supplemented with 47 g NS oil/kg CFM and control group. On contrary, Abou-Zeina et al (2015) found that Hb value was significantly increased when crushed black seeds supplemented by about 2% to diet of goats compared to control group.…”
Section: Hemoglobin Concentrationsupporting
confidence: 92%
See 3 more Smart Citations
“…Data in Table (7) eleducated that Hb values were nearly similar in different groups (12.55, 12.42 and 12.24 g/dL for G3, G2 and control group, respectively). These findings matches with those reported by Abd El-Halim et al (2014) who found that Hb values did not differ between sheep fed on diet supplemented with 47 g NS oil/kg CFM and control group. On contrary, Abou-Zeina et al (2015) found that Hb value was significantly increased when crushed black seeds supplemented by about 2% to diet of goats compared to control group.…”
Section: Hemoglobin Concentrationsupporting
confidence: 92%
“…This increase in WBCs count might be attributed to the emergence of these cells from the sites of composition in the bone marrow into the circulatory system due to the effects of some hormonal factors, affected by NS (Mbassa and Poulsen 1991). On contrary, Abd El-Halim et al (2014) demonstrated that the general effect of NS oil on WBCs in sheep was significantly lower compared to control group. Habeeb and El-Tarabany (2012) found that WBCs values were not affected by NSS additives to concentrate ration compared to basal ration.…”
Section: White Blood Cells Countmentioning
confidence: 94%
See 2 more Smart Citations
“…Supplementation of NS meal to 2 nd and 3 rd groups increased (P˂0.05) the WBCs and PCV% than their values in ewes of control group. The results of RBCs and Hb values agreed with those reported by Abd El-Halim et al (2014) who stated that these values did not affected in sheep fed ration supplemented with NS oil. Results of WBCs agreed with Res.…”
Section: Liver Functionsupporting
confidence: 90%